Jurnal PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS XI IPS MAS GEWAYANTANA KECAMATAN SOLOR TIMUR KABUPATEN FLORES TIMUR - Muhamad Fitrawan Syawal; Muhammad Syahrul; Bambang Sampurno; Mustamin; Maryam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The history of Islamic culture has a function, namely to enrich knowledge so that it can be useful for the continuation of education that will be undertaken by students, to make Muslims better individuals, and to support the development of Islam. This type of research is Classroom Action Research (PTK) using the research procedure approach of cycle I and cycle II. The key instruments of this research are SKI teachers and students of class XI IPS at MAS Gewayantana, East Solor Sub-district, East Flores Regency by using observation, interview, test, and documentation guidelines. Based on the results of the research conducted, it shows that; (1) The learning process in class XI IPS MAS Gewayantana East Solor District, East Flores Regency in the subject of Islamic Cultural History using the Cooperative Script learning model with group method learning strategies and student presentation schemes explaining to classmates has improved, both in terms of learning and learning outcomes. Thus, this learning activity ended in cycle II. (2) Pre-cycle in this study, the learning outcomes of students were classified as not reaching the average learning completeness (KKM) determined by the subject teacher, namely there were only 25.81% who reached the completeness of the scores of 31 students. In cycle I conducted by researchers, student learning outcomes increased to 48.38%. This was achieved in the implementation of cycle II carried out by researchers and achieved a very good increase, namely reaching 87.10% of students had achieved an increase in learning outcomes in the subject of Islamic Cultural History (SKI).